Anies Baswedan’s Directive Speech Act In Greeting Speech Of The 434th Anniversary of DKI Jakarta - Farhan Muhamad (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This study aims to describe the types, functions, and effects of directive speech acts in the greeting speech delivered by Anies Baswedan in the commemoration ceremony of the 494th anniversary of DKI Jakarta. The research approach used in this research is a theoretical and methodological approach. The theoretical approach used is a pragmatic approach, while the methodological approach used is a descriptive and qualitative approach. The data in this study are fragments of Anies Baswedan's speech, while the data source for this research is Anies Baswedan's welcoming speech in a YouTube video uploaded by the DKI Jakarta Regional Government. Data collection was carried out using the listening method with the basic technique, namely tapping technique, followed by an advanced technique, namely the conversational free listening technique which was then followed by recording and note-taking techniques. Data analysis using heuristic method. Presentation of the results of data analysis using informal methods. The results of the research in Anies Baswedan's speech found various variations of speech. Based on the types of speech acts found are directive speech acts inviting, asking, ordering, and advising.